DESCRIPTIVE ANALYSIS OF ORGANIZATIONAL CULTURE AT SYARIAH HOTEL DIAMOND: Array - Mutqi Sopiawadi; Reza Achmad Fahrezi; Tigin Lugiani (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
This research aims to describe the implementation of organizational culture at Diamond Subang Hotel, which adopts a sharia-based operational model. Using a qualitative descriptive approach, data was collected through interviews with hotel management and staff. The results show that the organizational culture at Diamond Subang Hotel places great emphasis on sharia principles, cleanliness, comfort, and friendly, professional service. This includes providing halal food, implementing a modest dress code, and creating a conducive environment for Muslim guests. The implementation of sharia-based values not only enhances customer loyalty and satisfaction, but also contributes to a positive image and increased hotel occupancy rates. Cleanliness and comfort are key focuses, aligning with Islamic teachings, while staff training programs support the development of professional and friendly services. This research demonstrates that a strong organizational culture in accordance with sharia principles offers a competitive advantage in the hospitality industry.